Historiography of Malay Islam in the Archipelago between Academic Archives and Sanad Tradition - Ibnu Da’i Munis; Irfan Musonif; Kholid Mawardi (Penerbit Hellow Pustaka, 2026)
This article examines the epistemological encounter between modern academic historiography and genealogical-spiritual narratives in the history of Malay–Nusantara Islam. The study employs a qualitative approach with a historical-comparative design based on library research. Data were collected from religious manuscripts, sanad and ulama genealogical documents, Islamic historiographical works, academic archives, and reputable scholarly publications, which were analyzed using historical source criticism, discourse analysis, and Pierre Bourdieu’s sociological framework of habitus, symbolic capital, and field. The findings reveal that Malay–Nusantara Islamic historiography develops through a dual epistemology that integrates the empirical validation of academic historiography with the legitimacy of sanad and spiritual authority embedded in genealogical traditions. Academic historiography emphasizes objectivity, archival evidence, and chronological consistency, whereas genealogical narratives prioritize sanad, lineage, and collective memory as the basis of historical legitimacy. The study further demonstrates that pesantren, Sufi orders, and ulama networks function as arenas for reproducing symbolic capital that sustains genealogical historiography amid the dominance of modern epistemology. Therefore, dual epistemology offers a framework for constructing a more inclusive, multidimensional, and contextual historiography of Islam in the Malay–Nusantara world.